Seminar Nasional Menggali Potensi Diri Membentuk Karakter Anak Yang Kreatif Melalui Proses Pendidikan Di Sekolah Dasar Swasta Muhammadiyah Kecamatan Lirik Kabupaten Indragiri Hulu - Kurniawan, Reyhan Exsa; Satria, Khevin Agna; Na’imah; Putri, Saffana Kiyasa; Rialdi; Wilanda, Aini; Ahmad, Fairuza Salsabila; Johni, Puti Qamara; Rahma, Nurliyanti; Hasugian, Prisko Ivan Savanger; Marhadi, Hendri (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2024)
Kuliah Kerja Nyata (KUKERTA) is an academic activity carried out by students in the form of community service. Through this service, students gain experience interacting and socializing with the community while contributing to solving problems within the society. As part of their service, KUKERTA students from the University of Riau organized a national seminar to develop the character and potential of children in the villages of Lambang Sari I, II, and III. The seminar aims to provide understanding and strategies to teachers, parents, and other educators on how to develop the potential and creative character of children in these villages. By involving discussions with experts in the field of education, the seminar emphasizes the crucial role of teachers in enhancing creativity and guiding children to become strong, character-driven individuals. The outcomes of this activity show that an educational approach integrating religious values, creativity, and local culture is highly effective in shaping creative and morally upright character in children. Additionally, the seminar highlights the importance of collaboration between schools and parents in optimally facilitating the development of children's potential.